Calorimetric study of carbon dioxide (CO2) hydrate formation and dissociation processes in porous media. (31st December 2022) - Benmesbah, Fatima Doria; Clain, Pascal; Fandino, Olivia; Osswald, Veronique; Fournaison, Laurence; Dicharry, Christophe; Ruffine, Livio; Delahaye, Anthony
Highlights: Calorimetric study of CO2 hydrates formation and dissociation in silica sand and gel. Induction time of CO2 hydrates is not influenced by water saturation. Silica sand of particle size of have a great effect on the amount of hydrates formed. Morphology of porous medium used have a big impact on the amount of hydrates formed. Better results have been obtained with silica gel than Fontainebleau sand. Abstract: Understanding the formation and dissociation mechanisms of gas hydrate in porous media is important for the development of new energy-efficient and environmentally friendly technologies related to cold storage as they provide significant latent heat and energy density at suitable phase change temperature. The challenge is to understand the interactions between gas hydrates and the chosen storage media in order to assess the operating conditions likely to optimize time and energy consumption in cold production and storage systems. In this work, CO2 hydrates formation and dissociation are investigated in two morphologically different porous materials: sand and silica gels. A calorimetric approach is applied to study both the CO2 hydrate formation kinetics, particularly the induction time, and the amount of hydrate formed for each of the two porous materials. The experiments are performed using a differential thermal analysis device with two identical measuring cells. The present work is focused on assessing the effect of key factors like water saturation, particle size and the morphology of porous media on CO2 hydrate formation and dissociation processes. Overall, the results do not show a statistically significant correlation between these factors and the induction time. Interestingly, the results obtained with dual porous silica gel showed a higher amount of hydrate formed compared to those with sand for similar initial pressure, temperature and water content conditions. This result may be due to the fact that silica gels provide higher surface area due to their smaller particle size (20–45 µm vs 80–450 µm for sand), and the presence of internal pore volume in silica gel particles.